Micropropagation of Tongkat Ali (Eurycoma Longifolia Jack) Via Somatic Embryogenesis and Direct Plant Regeneration Techniques - Hussein, Sobri (2004)
Eurycoma longifolia Jack or Tongkat Ali is well known among the local communities mainly for its aphrodisiac properties and its effectiveness as the cytotoxic, anti-malarial, anti-ulcer, anti-tumor promoting and anti-parasitic agent. In view of its potential commercial value as a plantation crop as well as to conserve its germplasm, the somatic embryogenesis and direct plant regeneration of E. longifolia were carried out as these in vitro micropropagation protocols had not been reported.